(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Most prevalent and well-liked techniques are those that measure the overall effectiveness of the device. Total productive maintenance is a frequent strategy utilized. In this project, we’ll use TPM to compute OEE and work through issues specific to a chosen industry. We gather machine shop data from the various industries, and after that, we determine the maximum OEE. The ideal OEE value is around 96%.